Abbreviated dual antiplatelet therapy after PCI in patients at high bleeding risk: a collaborative meta-analysis of randomized trials. (3rd October 2022) - Costa, F; Montalto, C; Bhatt, D; Steg, P G; Feres, F; Cao, D; Micari, A; Stone, G; Mehran, R; Valgimigli, M
Abstract: Aims: The optimal duration of dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) in patients at high bleeding risk (HBR) is still debated. We appraised an abbreviated compared with a more prolonged DAPT regimen in this setting by using the totality of existing evidence. Methods and results: A systematic review and meta-analysis was performed to search randomized clinical trials comparing abbreviated (i.e., short [3 months] or very-short [1 month]) with standard (≥6 months) DAPT in HBR patients. Six trials with 8, 409 patients were included. Major or clinically relevant non-major bleeding (MCRB) and major adverse cardiovascular events (MACE) were the co-primary safety and efficacy endpoints. MCRB was lower with abbreviated compared to standard DAPT (risk ratio [RR] 0.63, 95% CI 0.41–0.95; I 2 =74%). No difference in terms of MACE (RR 1.03, 95% CI 0.89–1.20; I 2 =0%) all-cause death, cardiovascular death, stent thrombosis or myocardial infarction were observed. Network meta-analysis showed short or very-short DAPT to have the highest probability to prevent bleeding in HBR patients. Conclusion: Abbreviated DAPT reduced bleeding without apparent increase in ischemic events in HBR patients undergoing PCI. Three-month or one-month DAPT courses appeared similarly effective to optimize the trade-off for ischemia and bleeding in this population. Funding Acknowledgement: Type of funding sources: None.